Черный трибунал. Бешеный против Лютого - Доценко Виктор (Вагриус, 2000)
Экземпляры: Ф. 12 (20200323) / Инвентарный номер: 44688 / Цена: 57.00 / Сис.шифр: 84(2=411.2)6-44 / Авт.знак: Д 71 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-44